Erving Manuel Goffman: biographical sources of sociological imagination - Shalin, Dmitri N. (New York and London Routledge, 2025)
Erving Goffman is the most cited American sociologist. There is no shortage of studies exploring Goffman$1 (Bs scholarship but no extant biography of Erving Goffman. The chief reason is that a man who looked behind the facades people erect to protect their private selves, zealously guarded his own backstage. This book is the first comprehensive biography of Goffman, an intellectual of Russian-Jewish descent, who turned the (3z(BPotemkin village(3y (Btrope into a powerful research program. The present study shows how key turns in Goffman$1 (Bs career reflected dramatic events in his family and personal history. It is based on the materials gathered in the Erving Goffman Archives, a repository curated by the author who has been collecting documents and conducting interviews with Goffman$1 (Bs relatives, colleagues, and friends. The archival work turned up documents which improve our understanding of Goffman the scholar, the teacher, and the man. The approach adopted in this investigation sheds new light on Goffman$1 (Bs scholarship which has had an enormous and continuous impact across the social sciences and humanities.s
Keywords: Social Sciences; Sociology & Social Policy; Political Sociology